CREATING A SHORT VIDEO “SIAPA SANGKA?” AS A REPRESENTATION OF THE IRONY OF UNIVERSITY STUDENT LIFE IN TIME MANAGEMENT - Daffa, Muhammad; Prameswari, Nadia Sigi (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
The creation of this short video, titled “Siapa Sangka?”, effectively conveys the irony of the lives of students who face challenges in time management. This video tells the story of students who are exhausted due to the pressure of assignments and often find that expectations do not match reality. This work aims to educate students on the importance of time and emotion management in academic life. Using elements of humor and suspense as a bridge, this short video serves not only as entertainment but also as an effective educational tool. Using a qualitative descriptive method, the production of this short video involves observation and interviews with students, following the stages in film production, which include pre-production, production, and post-production. The results of this production demonstrate that the short video “Siapa Sangka?” effectively conveys relevant social messages about student life, particularly in terms of navigating a time filled with uncertainty.